The Effects of Exchange Rate Liberalization in Kenya on French Beans Exports - Mwangi, Samuel Chege; Mbatia, Oliver L.E; Nzuma, Jonathan Makau (International Journal of Business, Economics and Management, 2014)
The adoption of a floating exchange rate system in Kenya was an effort to make it more aligned to the market determined equilibrium rate. However, there is limited empirical evidence that success has since been achieved in realizing the objective for which the foreign exchange market was liberalized. The exports of French beans are one of the leading contributors to foreign exchange earnings in Kenya. Nevertheless, the economic impacts of exchange rate liberalization on French beans exports in Kenya are unclear. This paper evaluates the magnitude and direction of the effects of exchange rate liberalization on French beans exports from Kenya to its major trading partners in the European Union. Monthly data for a fixed exchange regime represented by the period from 1990-1993 and a flexible regime represented by the period from 1994-2011 was used in the estimation of an export demand model. The empirical results show that the liberalization of the exchange rate led to an increase in the French beans export volumes from Kenya to the European Union. The paper recommends that, even if the Kenyan exchange rate system is flexible, exchange rate stability is necessary to avoid adverse effects of exchange rate volatility on French beans exports. Therefore, stability of the exchange rate is needed, not at a fixed level but by controlling exchange rate volatility using the exchange rate target band.